x-42=67

Simple and best practice solution for x-42=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-42=67 equation:


Simplifying
x + -42 = 67

Reorder the terms:
-42 + x = 67

Solving
-42 + x = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '42' to each side of the equation.
-42 + 42 + x = 67 + 42

Combine like terms: -42 + 42 = 0
0 + x = 67 + 42
x = 67 + 42

Combine like terms: 67 + 42 = 109
x = 109

Simplifying
x = 109

See similar equations:

| 3.5x+4forx=8 | | 1/7-5i | | -12t^2+108=0 | | s-1/3=4/9=7/9 | | 4.75=x+(-.25) | | x=3/4x+2 | | 2=3/4x+2 | | 3(4x+1)=-(2x-1) | | 3ln(x+2)+1=13 | | -2x+6=8x+-4 | | 6p^2+p-32=0 | | 2r-12=-12+3r | | 5x-3=(8x+11.5)-(3.5x+7.5) | | -1.4c=2.8 | | Y^2-x^2=-56 | | 6p^2-85p-160=0 | | -5t^2-20t+15=0 | | 5k-6/4=4 | | 4y-5(3y+10)=126 | | 5x-3=(8x-11.5)-(3.5x+7.5) | | x-39=9 | | (7-8i)/(-6i) | | Y/4-10=4 | | 5x+4-1=-9 | | (2/9)(2/9 | | x-51=68 | | 25w^3-20w^2=0 | | 5x+11=(11.5-7)-(4.5-2) | | 2x^2-xy+y^2=4 | | -.01t=ln(t-68)-ln(97) | | 2x(x-1)=3x-4 | | 2(1x-8)+1x=3(x-6)+2 |

Equations solver categories